1995
DOI: 10.1136/bjo.79.9.847
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interferon alfa and gamma on human uveal melanoma cells in vitro.

Abstract: Background-Uveal melanoma is a tumour with a high incidence of metastasis and a high mortality rate. Additional therapies to obtain a better local control or an effective treatment ofmetastases are necessary. Interferons may be applied. Methods (Br_J Ophthalmol 1995; 79: 847-855) In recent years the anti-tumour activities of interferons (IFNs) have been studied extensively. Promising therapeutic results have been reported, especially in the treatment of haematological malignancies. 1-3 IFNs may also be of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
0
20
1
Order By: Relevance
“…In contrast to in vitro data that suggested activity of interferon alfa on human uveal melanoma cell lines, 53 immunotherapy with interferon administered alone or with interleukin-2 in 21 patients resulted in only 2 minor responses. 31 We observed no responses with interferon alfa-2b administered by hepatic arterial infusion to 16 patients with metastatic choroidal melanoma confined to the liver.…”
Section: Intravenous Chemotherapycontrasting
confidence: 74%
“…In contrast to in vitro data that suggested activity of interferon alfa on human uveal melanoma cell lines, 53 immunotherapy with interferon administered alone or with interleukin-2 in 21 patients resulted in only 2 minor responses. 31 We observed no responses with interferon alfa-2b administered by hepatic arterial infusion to 16 patients with metastatic choroidal melanoma confined to the liver.…”
Section: Intravenous Chemotherapycontrasting
confidence: 74%
“…Biochemotherapy has had limited evaluation for efficacy against metastatic uveal melanoma. In contrast to in-vitro data which suggests that interferon-a has an action on human melanoma cell lines [14], immunotherapy with interferon-a-2b administrated alone or with interleukin-2 has shown only few minor responses [15]. The experience with cutaneous melanoma has shown that biochemotherapy is superior to chemotherapy alone with regard to response rate and progression-free survival but with similar overall survival and higher toxicity [16].…”
Section: Discussionmentioning
confidence: 93%
“…Several papers have shown that type I and type II IFNs can have variable effects on cell proliferation and integrin/adhesion molecule expression in uveal melanoma (12,13). Like cutaneous melanoma, the biology of uveal melanoma can also be affected through decitabine-induced gene re-expression.…”
mentioning
confidence: 99%